Analysis of microbial community structure in a biofilm on membrane surface in the submerged membrane bioreactor treating domestic wastewater on the basis of respiratory quinone profiles - Lim, BR; Ahn, KH (MICROBIOL RES FOUNDATION, 2004)
The objective of this study was to investigate the microbial community structure of the biofouling film formed on hollow-fiber membrane surfaces in the submerged membrane bioreactor (SMBR) with a nitrification-denitrification process. In this experiment, aeration was conducted intermittently (60 min off, 90 min on) cyclic anoxic and oxic conditions in the SMBR. The dominant quinone types of biofilm on the membrane surface in an intermittently aerated SMBR were ubiquinone (UQs)-8, -10, followed by menaquinones (MKs)-8(H-4), -8(H-2) and -7, but those of suspended microorganisms were UQ-8, UQ-10 followed by MKs-8, -9(H-4) and -6. The change in quinone profiles of biofilm on the membrane surface suggested that UQ-9, MK-7, MK-8(H-2) and MK-8(H-2) contributed to microbiological fouling in the intermittently aerated SMBR treating domestic wastewater. The microbial diversities of suspended microorganisms and biofilm, calculated based on the composition of all quinones, were 9.5 and 10.9, respectively.
Keywords: ACTIVATED-SLUDGE; BACTERIA